Blind nasal intubation as an alternative to difficult intubation approaches - Yoo, Hwanhee; Choi, Jae Moon; Jo, Jun-young; Lee, Sukyung; Jeong, Sung-Moon (Journal of dental anesthesia and pain medicine: JDAPM, 2015)
Airway difficulties are a major concern for anesthesiologists. Even though fiberoptic intubation is the generally accepted method for management of difficult airways, it is not without disadvantages-requires patient cooperation, and cannot be performed on soiled airway or upper airways with pre-existing narrowing pathology. Additionally, fiberoptic bronchoscopy is not available at every medical institution. In this case, we encountered difficult airway management in a 71-year-old man with a high Mallampati grade and a thick neck who had undergone urologic surgery. Several attempts, including a bronchoscope-guided intubation, were unsuccessful. Finally, blind nasal intubation was successful while the patient's neck was flexed and the tracheal cartilage was gently pressed down. We suggest that blind nasal intubation is a helpful alternative in difficult airway management and it can be a lifesaving technique in emergencies. Additionally, its simplicity makes it a less expensive option when advanced airway technology (fiberoptic bronchoscopy) is unavailable.